Efficacy and Safety of Flibanserin in Women with Hypoactive Sexual Desire Disorder: A Systematic Review and Meta-Analysis. (1st November 2015) - Gao, Zhenli; Yang, Diandong; Yu, Luxin; Cui, Yuanshan
Abstract: Introduction: Flibanserin, is a postsynaptic agonist of serotonin receptor 1A and an antagonist of serotonin receptor 2A, has been shown to increase sexual desire and reduce distress in women with hypoactive sexual desire disorder (HSDD). Aim: We carried out a systematic review and meta-analysis to assess the efficacy and safety of the drug in women with HSDD. Methods: A literature review was performed to identify all published randomized double-blind, placebo-controlled trials of flibanserin for the treatment of HSDD. The search included the following databases: MEDLINE, EMBASE, and the Cochrane Controlled Trials Register. The reference lists of the retrieved studies were also investigated. Main Outcome Measures: Four publications involving a total of 3, 414 patients were used in the analysis, including four randomized controlled trials that compared flibanserin with placebo. Results: For the comparison of flibanserin with placebo, primary efficacy endpoints: satisfying sexual events (the standardized mean difference [SMD] = 0.59, 95% confidence interval [CI] = 0.37–0.80, P < 0.00001); sexual desire score (the SMD = 1.91, 95% CI = 0.21 to 3.60, P = 0.03) and Female Sexual Function Index (FSFI) desire domain score (the SMD = 0.32, 95% CI = 0.19–0.46, P < 0.00001) and key secondary efficacy endpoints: FSFI total score, Female Sexual Distress Scale-Revised (FSDS-R) total score, FSDS-R Item 13 score, Patient's Global Impression of Improvement score and Patient Benefit Evaluation indicated that flibanserin was more effective than the placebo. Safety assessments included the proportion of women who experienced an adverse event (odds ratio = 1.54, 95% CI = 1.34 to 1.76, P < 0.00001), nervous system disorders and fatigue indicated that flibanserin was well tolerated. Conclusions: This meta-analysis indicates that flibanserin to be an effective and safe treatment for HSDD in women.